2021
DOI: 10.1111/hae.14444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a supervised therapeutic exercise program on musculoskeletal health and gait in patients with haemophilia: A pilot study

Abstract: Introduction Episodes of bleeding in patients with haemophilia (PwH) are associated with haemophilic arthropathy, limitations in physical performance, reduced quality of life (QoL), and gait disorders. Aim This non‐randomized, controlled, interventional, prospective, single‐centre pilot study aimed to assess the effects of an 8‐week supervised therapeutic exercise program on musculoskeletal health, gait kinematic parameters (GKP), functional capacity, and QoL in adult PwH. Methods Nineteen PwH were allocated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Among the studies included, ten studies performed the 6MWT in a corridor of at least 20 m or reported compliance with American Thoracic Society guidelines and were included in the secondary analysis 22,26,27,29,30,33–37 . Four studies were excluded from the secondary analysis, two for using a corridor of less than 20 m (i.e., 8 and 15 m) 12,32 and two studies for not reporting corridor length or not adhering to technical guidelines 28,31 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the studies included, ten studies performed the 6MWT in a corridor of at least 20 m or reported compliance with American Thoracic Society guidelines and were included in the secondary analysis 22,26,27,29,30,33–37 . Four studies were excluded from the secondary analysis, two for using a corridor of less than 20 m (i.e., 8 and 15 m) 12,32 and two studies for not reporting corridor length or not adhering to technical guidelines 28,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies assessed physical capacity using the 6MWT 12,22,26–37 . In children, the distance walked ranged from 274 ± 36 30 to 680 ± 100 m 26 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations